Pengaruh Penerapan E-litigation Terhadap Proses Cerai Gugat Pada Pengadilan Agama Merauke - Khaerul Firman Mustari; Rizky Ramadhan Baried (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
ABSTRACT In this technological era, the Supreme Court of the Republic of Indonesia has implemented a form of digital service to create a simple, fast, and low-cost judicial system, namely e-court and e-litigation. It being implemented in court below supreme court entirely, one of them is Islamic court. The formulation of the problem in this study are: How does the application of e-litigation affect the divorce process at the Merauke Islamic Court? How are the efforts of the Merauke Islamic Court in encouraging justice seekers (plaintiffs/applicants) to proceed with e-litigation? The research method used is empirical legal research with a statutory approach and a sociological juridical approach. The results in this study are the effect of the application of e-litigation on the divorce process at the Merauke Islamic Court so far has not been running effectively, due to inadequate human resources and the lack of technological knowledge. The efforts of the Merauke Islamic Court in encouraging justice seekers (plaintiffs/applicants) to proceed with E-litigation are to carry out the socialization through the Merauke Islamic Court website, distributing brochures to the public, socializing in districts that are the jurisdiction of the Merauke Islamic Court.